IDENTIFIKASI MUTASI GEN CYSTATIONINE-β SYNTHASE (CBS) DAN GEN METHYLENETETRAHYDROFOLATE REDUCTASE (MTHFR) PADA PENDERITA PREMATUR INFARK MIOKARD AKUT DENGAN HIPERHOMOSISTEINEMI - Muliartha, I Ketut Gede; Sargowo, Djanggan; Iskandar, Abdillah (Jurnal Kedokteran Brawijaya, 2008)
ABSTRACT Hyperhomocysteinemia appears to be an independent risk factor for coronary heart disease. Elevated levels of  plasma  total  homocysteine  (tHcy)  was  caused  by  genetic  or  nutrient-related  disturbances  in  the transsulfuration  or  remethylation  pathways  for  homocysteine  metabolism.  This  study  observed  premature myocard  infarct  acute  patients  with  hyperhomocysteinemia.The  aim  of  the  research  was  to  determine Cystarhionine-β  Synthase  and  Methylenetetrahydrofolate  Reductase  genes  mutations  in  premature  acute myocard  infarct  patients  with  hyperhomocysteinemia.This  study  was  a  cross  sectional  study  in  premature acute myocard infarct patients. Twenty three patients were examined for plasma total homocysteine, vitamin B6, vitamin B12 folic acid and lipid profile. Total DNA isolated from patients with hyperhomocystememia and normal  folic  acid,  vitamin  B6,  vitamin  B12  levels  and  lipid  profile.  Five  patients  were  assayed  for Cystathionine-β  Synthase  and  gen  Methylenetetrahydrofolate  Reductase  genese  mutations  by  Polymerase Chain  Reactions  (PCR).  Five  from  23  patients  (  21,7%  )  plasma  total